Improving behaviour in self-testing (IBIS): Study on frequency of use, consequences, information needs and use, and quality of currently available consumer information (protocol) - de Vries Nanne K; Ickenroth Martine HP; Grispen Janaica EJ; Dinant Geert-Jan; Ronda Gaby; van der Weijden Trudy (BMC, 2010)
Abstract Background Self-tests are available to consumers for more than 25 conditions, ranging from infectious diseases to cardiovascular risk factors. Self-tests are defined as in-vitro tests on body materials such as blood, urine, faeces, or saliva that are initiated by consumers to diagnose a particular disorder or risk factor without involving a medical professional. In 2006, 16% of a sample of Dutch Internet users had ever used at least one self-test and 17% intended to use a self-test in the future. The objectives of this study are to determine (1) the frequency of self-test use, (2) the consumers' reasons for using or not using a self-test, (3) the information that is used by self-testers in the different self-test stages and the consumers' interpretation of the quality of this information, (4) the consumers' response to self-test results in terms of their confidence in the result, reassurance by the test result, and follow-up behaviour, (5) the information consumers report to need in the decision making process of using or not using a self-test, and in further management on the basis of the self-test result, and (6) the quality of the currently available consumer information on a selected set of self-tests. Methods Mixed methods study with (1) a cross-sectional study consisting of a two-phase Internet-questionnaire, (2) semi-structured interviews with self-testers and consumers who intend to use a self-test, and (3) the assessment of the quality of consumer information of self-tests. The Health Belief Model and the Theory of Planned Behaviour will serve as the theoretical basis for the questionnaires and the interview topic guides. Conclusions The self-testing area is still in a state of flux and therefore it is expected that self-test use will increase in the future. To the best of our knowledge, this is the first study which combines quantitative and qualitative research to identify consumers' information needs and use concerning self-testing, and the consumers' actual follow-up behaviour based on the self-test result, and simultaneously investigates the quality of the currently available consumer information. The results of this study will be used as an input in developing consumer information on self-testing.